Description of Fear of Missing Out (FoMO) in Students and Implications for Guidance and Counseling - Khairunnisa, Azizah; Putriani, Lisa; Taufik, Taufik; Adlya, Soeci Izzati; Putra, Ade Herdian (Universitas Negeri Padang, 2025)
The phenomenon of Fear of Missing Out (FoMO) has become increasingly relevant among adolescents due to the increased use of social media. FoMO refers to a psychological condition characterized by anxiety and fear of missing out on information or experiences that others may have, especially online. This study aims to explore the level of FoMO in high school students and its implications for guidance and counseling services. The approach used was a quantitative method with descriptive analysis. The study sample was obtained through stratified random sampling, with 262 students at SMA Negeri 3 Padang as respondents. Data analysis was conducted descriptively using Microsoft Excel and SPSS. The results revealed that 46.18% of students experienced moderate levels of FoMO. This study contributes novelty by examining FoMO in high school students, an age group vulnerable to the influence of social media. These findings suggest the need for significant guidance and counseling interventions to help reduce FoMO among students. Future research is encouraged to expand this study by examining FoMO in relation to other variables.